2022
DOI: 10.3390/horticulturae8100964
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation of Pyracantha angustifolia (Franch.) C.K. Schneid.

Abstract: Narrow-leaf firethorn or pyracantha (Pyracantha angustifolia (Franch.) C.K. Schneid.), from the family Rosaceae, is a species of large and thorny evergreen shrub. In this study, a procedure is presented for efficient axillary shoot multiplication and root induction in P. angustifolia using Murashige and Skoog (MS), woody plant (WPM), and Linsmaier and Skoog (LS) culture media supplanted with 6-benzylaminopurine (BAP) and indole-3-butyric acid (IBA). The disinfection of the axillary buds was performed with a 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…genotypes 'Kashan' and 'Hervy Azerbaijan'. Previous studies revealed that PGRs play a vital role in enhancing the in vitro propagation efficiency of many species belonging to the Rosaceae family [7,29,30], which corresponds with our results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…genotypes 'Kashan' and 'Hervy Azerbaijan'. Previous studies revealed that PGRs play a vital role in enhancing the in vitro propagation efficiency of many species belonging to the Rosaceae family [7,29,30], which corresponds with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Usually, the optimum concentration of PGRs for maximum shoot multiplication and root induction is not only species-specific, but also varies between genotypes, cultivars, and explant types, which is related to the different content of endogenous hormones [7,17]. Interestingly, in the present study, the highest number of shoots, in both genotypes studied, was produced in the same culture medium, i.e., MS containing 2 mg•L −1 BAP and 0.4 mg•L −1 GA 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As there are few differences among the basal media used, it is quite difficult to identify the exact nutrient that promotes the growth in MS, but this could be the high level of NH 4 NO 3 present in MS, which is four times higher than that in QL and WPM. In general, MS is the most widely used medium to support tissue culture across a broad range of plant species [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%